Circulating Myeloperoxidase (MPO)-DNA complexes as marker for Neutrophil Extracellular Traps (NETs) levels and the association with cardiovascular risk factors in the general population. - Samantha J Donkel; Frank J Wolters; M Arfan Ikram; Moniek P M de Maat (PLoS ONE, 2021)
Introduction Neutrophil extracellular traps (NETs) are DNA scaffolds enriched with antimicrobial proteins. NETs have been implicated in the development of various diseases, such as cardiovascular disease. Here, we investigate the association of demographic and cardiovascular (CVD) risk factors with NETs in the general population. Material and methods Citrated plasma was collected from 6449 participants, aged ≥55 years, as part of the prospective population-based Rotterdam Study. NETs were quantified by measuring MPO-DNA complex using an ELISA. We used linear regression to determine the associations between MPO-DNA complex and age, sex, cardio-metabolic risk factors, and plasma markers of inflammation and coagulation. Results MPO-DNA complex levels were weakly associated with age (log difference per 10 year increase: -0.04 mAU/mL, 95% confidence interval [CI] -0.06;-0.02), a history of coronary heart disease (yes versus no: -0.10 mAU/mL, 95% CI -0.17;-0.03), the use of lipid-lowering drugs (yes versus no: -0.06 mAU/mL, 95% CI -0.12;-0.01), and HDL-cholesterol (per mmol/l increase: -0.07 mAU/mL/, 95% CI -0.12;-0.03). Conclusions Older age, a history of coronary heart disease, the use of lipid-lowering drugs and higher HDL-cholesterol are weakly correlated with lower plasma levels of NETs. These findings show that the effect of CVD risk factors on NETs levels in a general population is only small and may not be of clinical relevance. This supports that NETs may play a more important role in an acute phase of disease than in a steady state situation.